Occupational Health and Safety, Risk Assessment, and Management in the Machinery Sector - Abduladeem A. A. belkher; Masood A. Masood (African Journal of Advanced Pure and Applied Sciences, 2023)
The machinery sector plays a vital role in economic development but is also associated with significant occupational health and safety (OHS) risks. This study investigates OHS practices, risk assessment stages, and management strategies in the machinery sector. A comprehensive literature review was conducted to gather relevant information. The study examines hazard identification, risk analysis, and risk evaluation as stages in the risk assessment process. It also investigates management strategies to control and mitigate identified risks. The findings reveal numerous OHS challenges in the machinery sector, including machine-related accidents, exposure to hazardous substances, and ergonomic issues. Proactive measures like safety training programs, guidelines, and personal protective equipment are essential for effective risk mitigation. Overall, this study contributes to existing knowledge on OHS practices and risk assessment in the machinery sector. It provides insights into the risk assessment process and offers practical recommendations to promote a safe and healthy working environment. Implementing these measures can reduce workplace accidents, improve worker well-being, and enhance productivity in the machinery sector.